Jaw-opening oromandibular dystonia secondary to Wilson's Disease treated with botulinum toxin type A - Hélio A.G. Teive; Leandro E. Klüppel; Renato P. Munhoz; Nílson Becker; Paulo R. Müller; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria)
We have reported a case series of five patients with jaw-opening oromandibular dystonia secondary to Wilson's disease (WD), in which the patients were treated with botulinum toxin type A (BTX-A). In all cases, dystonia score was partially reduced three weeks after injections. The most common side effect was transient mild dysphagia. This preliminary study showed that jaw-opening oromandibular dystonia in WD may be partially responsive to the use of BTX-A.